Identifying faculty opinions about implementing an online, non-thesis master’s degree - Maynard, Rebekah C. I.; Pennisi, Svoboda V.; Lombardini, Leonardo (Frontiers in Education, 2023)
Although distance education is a growing field, there are benefits and challenges in creating and implementing new online degrees based on differing perceptions about online learning. The purpose of this research was to identify faculty opinions about implementing an online, non-thesis master’s degree as an alternative to the existing thesis-based degree. In this study, 17 faculty members in the field of horticulture were surveyed at a major university in the southeastern United States. Using Q methodology for qualitative and quantitative analysis, three distinct perspectives were summarized as: (A) in-person instruction is more effective than online education, (B) online programs increase accessibility to graduate degrees, and (C) successful online programs require independent learners. Based on these faculty perspectives, it is believed that an online, non-thesis master’s would be successful if faculty were trained to be effective online educators and if they encouraged students to hold a deeper level of engagement with the content.